Deciphering Effects of Uncontrolled Cytomegalovirus Replication on Immune Responses in Cytomegalovirus DNA-Positive Renal Transplant Recipients - Makwana, Nandini; Waters, Shelley; Irish, A.; Howson, P.; Price, Patricia (MARY ANN LIEBERT, INC, 2019)
Cytomegalovirus (CMV) is a highly prevalent virus and a common cause of morbidity in solid organ transplant patients. It is also known for its long-lasting imprint on the immune system, expanding populations of highly differentiated T cells and natural killer (NK) cells with novel phenotypes. However, it is unclear whether these cells mark success or failure in the management of an active infection. We assessed CMV reactivation in 54 renal transplant recipients (RTRs) by measuring CMV DNA in plasma samples. Function and phenotype of T cells and NK cells were then assessed in seven RTR with detectable CMV DNA. The patient with highest CMV viral load (P1) displayed increased NK cell function and abundant highly differentiated T cells. We compare P1 with the other six patients and review possible scenarios of cross-regulation between NK cells and T cells.